Monetary Policy Objectives During the Crisis: An Overview of Selected Southeast European Countries - Aneta Krstevska (Journal of Central Banking Theory and Practice, 2015)
The recent global crisis brought many challenges to the central bankers worldwide, including the issue of monetary policy objectives. In this view, besides price stability maintenance, a special attention by central bankers during the crisis was given to the output stabilization. This paper explores this issue on the case of a group of countries from Southeast Europe (SEE). For this purpose, rather simple analysis of the policy rate and output gap as well as output gap variability by countries have been provided, aimed at giving some initial insights of the monetary policy and output stabilization during the crisis. Our findings pointed that the central banks in the analysed SEE countries paid attention to the output stabilization, specifically during the crisis period and that was presumably enabled by controllable inflation developments.
Keywords: E52; E43; O52; 330; monetary policy; central banks; interest rates; output; crisis